2022
DOI: 10.1002/rmv.2348
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant/anti‐inflammatory effect of Mg2+ in coronavirus disease 2019 (COVID‐19)

Abstract: Severe acute respiratory syndrome coronavirus type 2 (SARS‐CoV‐2) causes coronavirus disease 2019 (COVID‐19), characterised by high levels of inflammation and oxidative stress (OS). Oxidative stress induces oxidative damage to lipids, proteins, and DNA, causing tissue damage. Both inflammation and OS contribute to multi‐organ failure in severe cases. Magnesium (Mg 2+ ) regulates many processes, including antioxidant and anti‐inflammatory responses, as well as the proper functioning of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 220 publications
1
20
0
Order By: Relevance
“…The demonstration that a combination of glycine and N-acetylcysteine supplementation rapidly improves GSH deficiency, oxidative stress and oxidant damage has implications for considering the GSH importance in combating COVID-19 infected patients warranting further investigations ( Kumar P. et al, 2022 ). Enzymes involved in GSH biosynthesis and function like γ-glutamyl-cysteine ligase and glutathione synthetase are completely dependent on ATP and require magnesium as a cofactor ( Bani Younes et al, 2020 ; Tang et al, 2020 ; Arancibia-Hernández et al, 2022 ). Additionally, γ-glutamyl-transpeptidase uses magnesium as an enzyme activator ( Arancibia-Hernández et al, 2022 ).…”
Section: Sars-cov-2 New Therapeutic Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…The demonstration that a combination of glycine and N-acetylcysteine supplementation rapidly improves GSH deficiency, oxidative stress and oxidant damage has implications for considering the GSH importance in combating COVID-19 infected patients warranting further investigations ( Kumar P. et al, 2022 ). Enzymes involved in GSH biosynthesis and function like γ-glutamyl-cysteine ligase and glutathione synthetase are completely dependent on ATP and require magnesium as a cofactor ( Bani Younes et al, 2020 ; Tang et al, 2020 ; Arancibia-Hernández et al, 2022 ). Additionally, γ-glutamyl-transpeptidase uses magnesium as an enzyme activator ( Arancibia-Hernández et al, 2022 ).…”
Section: Sars-cov-2 New Therapeutic Approachesmentioning
confidence: 99%
“…Enzymes involved in GSH biosynthesis and function like γ-glutamyl-cysteine ligase and glutathione synthetase are completely dependent on ATP and require magnesium as a cofactor ( Bani Younes et al, 2020 ; Tang et al, 2020 ; Arancibia-Hernández et al, 2022 ). Additionally, γ-glutamyl-transpeptidase uses magnesium as an enzyme activator ( Arancibia-Hernández et al, 2022 ). Magnesium supplementation improves mitochondrial function and increases the content of GSH in those organelles ( Liu et al, 2019 ; Mohammadi et al, 2020 ).…”
Section: Sars-cov-2 New Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial dysfunction and procoagulant status may explain the high incidence of thromboembolic events in patients with COVID-19 [ 72 , 84 , 85 ]. Magnesium deficits exacerbate the inflammatory response induced by SARS-CoV-2 and maintain and propagate the so-called cytokine storm, followed by acute respiratory distress syndrome, which favors the development of endothelial lesions and coagulopathy, the consequence of which is multiple organ dysfunction syndrome [ 84 , 85 , 89 ]. In addition, other symptoms that have been reported by patients with COVID-19, such as asthenia, myalgias, anxiety, depression, and insomnia, may be related to the presence of a Mg 2+ deficiency [ 84 , 90 , 91 ].…”
Section: Magnesium and Covid-19mentioning
confidence: 99%
“…The SHADE study [ 101 ] revealed that a higher proportion of vitamin D-deficient individuals with SARS-CoV-2 infection became SARS-CoV-2 RNA negative, with a significant decrease in the inflammatory marker (fibrinogen) on short-term, high-dose cholecalciferol supplements. Furthermore, it has been observed that concomitant supplementation with vitamin D, vitamin B12, and Mg 2+ in patients with COVID-19 may decrease the incidence of intensive care hospitalization and required oxygen therapy [ 89 , 102 ].…”
Section: Magnesium and Covid-19mentioning
confidence: 99%